Penerapan Pembelajaran Cooperative Integrated Reading And Presentation History (CIRPH) untuk Meningkatkan Aktivitas Belajar Dan Hasil Belajar Siswa - Prasetiyo, Eko; Deden Mutakin, Mohamad (SWADESI: Jurnal Pendidikan dan Ilmu Sejarah, 2025)
Cooperative Integrated Reading And Presentation History (CIRPH) is the development of a learning model from Cooperative Integrated Reading Compotition (CIRC) and the concept of historical literacy. The purpose of developing the CIRPH model in this study is to improve learning activities and learning outcomes. This research is a classroom action research design (PTK) with a qualitative approach of the Kurt Lewin Model model with 2 cycles consisting of four components (planning, treatment, observation and reflection). This research was conducted in XII MIA 1 (IPA 1) class of 31 students at Madrasah Mu'allimin Muhammadiyah Yogyakarta. Data collection using documentation, observation, and evaluation tests to measure learning outcomes after the application of CIRPH. Data validity was carried out through informant review and data reliability by compiling and storing data base and thick description. The results showed that the use of the CIRPH method development was able to improve students' creativity and learning outcomes. CIRPH is a learning method development that combines cooperative learning, integrated reading, and presentation in the context of history education. This development aims to improve students' understanding of historical literacy through cooperation in groups, in-depth reading analysis, and the ability to present findings or student learning outcomes.